A217 EXTERNAL VALIDATION OF THE PARK SCORE FOR BOWEL PREPARATION CLEANLINESS DURING CAPSULE ENDOSCOPY. (1st March 2018) - Alageeli, M H; Yan, B; Zepeda-Gomez, S; Alshankiti, S; Stitt, L; Thomas, B S; Bahreini, Z; Homenauth, R; Dang, T; ROFAIEL, R; Al-Zahrani, M; Townsend, C M; et al.
Abstract: Background: Capsule endoscopy is the test of choice for small intestinal diseases although it can be limited by poor bowel preparation. The Park score measures small intestinal cleanliness based on the % of mucosa visualized and % of view obstructed and is a promising tool for assessing small bowel preparation although further validation is required before it can be routinely used. Aims: The objective of this study was to externally validate the Park score among a large number of readers with varying levels of expertise in capsule endoscopy. Methods: A total of 20 readers consisting of 4 capsule endoscopists, 4 GI fellows, 4 internal medicine residents, 4 medical students, and 4 nurses were invited to participate in the study. All readers completed a web-based Training Module on the Park score followed by an Assessment Module which was repeated 4 weeks later. The Assessment Module consisted of 1, 233 images derived from 25 randomly selected capsule videos. Images were selected at 5 minute intervals between the first duodenal and first cecal images of each video and readers rated the % of the mucosa visualized and the % of view obstructed as defined by the Park score. The primary outcome was inter-observer and intra-observer agreement for the total score and secondary outcomes included stratification by subscores and reader group. Agreement was determined based on intraclass correlation coefficients. Results: The mean inter-observer and intra-observer agreement for the total Park score between all readers was 0.81 (95% CI 0.70–0.87) and 0.92 (0.87–0.94). Stratified by sub-scores, the mean inter and intra-observer agreement for % visualized mucosa was 0.79 (0.67–0.85) and 0.91 (0.86–0.93) and for % of view obstructed was 0.77 (0.64–0.84) and 0.91 (0.87–0.94). The agreement between capsule endoscopists and GI fellows, internal medicine residents, medical students, and nurses were 0.93 (0.88–0.97), 0.90 (0.82–0.95), 0.90 (0.82–0.95), 0.85 (0.74–0.92), respectively. Conclusions: The Park score is a simple and reliable scoring system to measure small intestinal cleanliness with excellent agreement between a wide range of readers with varying levels of experience with capsule endoscopy. Funding Agencies: None